If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x) * x(11x + 9) = 0 Remove parenthesis around (6x) 6x * x(11x + 9) = 0 Reorder the terms: 6x * x(9 + 11x) = 0 Multiply x * x 6x2(9 + 11x) = 0 (9 * 6x2 + 11x * 6x2) = 0 (54x2 + 66x3) = 0 Solving 54x2 + 66x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6x2'. 6x2(9 + 11x) = 0 Ignore the factor 6.Subproblem 1
Set the factor 'x2' equal to zero and attempt to solve: Simplifying x2 = 0 Solving x2 = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x2 = 0 Take the square root of each side: x = {0}Subproblem 2
Set the factor '(9 + 11x)' equal to zero and attempt to solve: Simplifying 9 + 11x = 0 Solving 9 + 11x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 11x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 11x = 0 + -9 11x = 0 + -9 Combine like terms: 0 + -9 = -9 11x = -9 Divide each side by '11'. x = -0.8181818182 Simplifying x = -0.8181818182Solution
x = {0, -0.8181818182}
| 8/5y=80 | | -4+6(-6-5n)=38-4n | | z=2/3=1/8 | | 3x+1=136 | | (3m^2-2d^4)+(4m^2+2m-5d)= | | lgx=-3.28 | | -2y-6=-14 | | 4x+1=149 | | (x+1)-(x^2+1)=0 | | 8/12x9/12 | | a-1.5(a+8)=4.5 | | -4+d=3 | | 0=q-14 | | lgx=-5 | | 8z+15=3z-20 | | y/6=-1 | | 7w+4=2(7w-5) | | (7x^2+17x+13)-(12x^2+10x+4)=0 | | 3y-4x=6Fory | | -3(r+7)=-55 | | 7y+2x=5 | | x=5y+8.75 | | 3(m+31)=33 | | (x+1)-(x^2+2)=0 | | 14=-7/9v | | 7t-11=24 | | 3x^2-2y^3+6x=0 | | -5(1+6x)+3x=21-x | | 4x-9=6x-21 | | X+y+(x+41)=887 | | -2/3n=32/9 | | y=1000(1.75)t |